Rapid Generation of EBV‐Specific Cytotoxic T Lymphocytes Resistant to Calcineurin Inhibitors for Adoptive Immunotherapy. Issue 12 (8th October 2013) - Ricciardelli, I.; Brewin, J.; Lugthart, G.; Albon, S. J.; Pule, M.; Amrolia, P. J.
Abstract Epstein–Barr virus (EBV)‐associated posttransplant lymphoproliferative disorder (PTLD) remains a major cause of morbidity and mortality after hematopoietic stem cell (HSCT) or solid organ transplant (SOT). Strategies to reconstitute immunity by adoptive transfer of EBV‐specific cytotoxic T lymphocyte (CTL) therapy while highly effective in the HSCT setting where immunosuppression can be withdrawn have been less successful in the SOT setting where continued immunosuppression therapy is necessary. Additionally, the complexity and time taken to generate EBV‐CTLs for adoptive transfer limit the clinical applicability. We have developed a system for the rapid generation of EBV‐CTLs resistant to immunosuppression based on selection of interferon‐gamma (IFN‐γ) secreting EBV‐CTLs and retroviral transduction with a calcineurin B mutant. With this methodology, EBV‐CTLs resistant to the calcineurin inhibitor Tacrolimus (TAC) can be produced in 14 days. These CTLs show high specificity for EBV with negligible alloreactivity in both proliferation and cytotoxicity assays and are able to proliferate and secrete IFN‐γ in response to antigen stimulation in the presence of therapeutic doses of TAC. This strategy will substantially facilitate clinical application of this approach for the treatment of PTLD in SOT recipients.